Efektivitas Terapi Sentuhan (Healing Touch) pada Anak Pasca Operasi di RSAB Harapan Kita Jakarta - Lameky, Vernando Yanry; Siahaya, Alisye; Lestari, Indri Puji (MOLUCCAS HEALTH JOURNAL, 2023)
Background: Healing Touch is a non-pharmacological therapy that utilizes gentle touch to restore the body's energy balance, reduce pain, and improve patient comfort. This therapy is relevant to be applied in post-operative pain management in children, which is often not optimal with a pharmacological approach alone. Objective: This study aims to evaluate the effectiveness of Healing Touch in reducing pain in children after surgery at RSAB Harapan Kita Jakarta. Method: This study used a quasi-experimental one-group pretest-posttest design involving 20 children as respondents. Pain levels were measured using the FLACC scale before and after the Healing Touch intervention for 30 minutes. Data analysis was performed using the Wilcoxon test to test differences in pain levels before and after the intervention. Results: Before the intervention, the majority of respondents (65%) experienced moderate pain (score 4–6), while after the intervention, 85% of respondents no longer felt pain (score 0). The average pain level decreased significantly from 5.15 to 0.45 (p 0.001). Conclusion: Healing Touch effectively reduces pain levels in children after surgery. This therapy can be used as an alternative holistic non-pharmacological pain management to improve the quality of child care.Keywords: healing touch; pain management; postoperative children; non-pharmacological therapy